FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR - Hafidhah Hasanah; Yohanes (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence about the factors that affecting tax aggressiveness. The independent variables used in this study are capital intensity, inventory intensity, firm size, firm risk, audit committee, and independent commissioners. The dependent variable used in this study is tax aggressiveness. The population of this research is manufacturing companies listed in Indonesia Stock Exchange from 2018 to 2020 period of 171 data. The method used to determine the sample is purposive sampling and there are 52 companies that met the criteria in this study with a total of 156 data. This research used multiple regression analysis model. The result shows that company size has an influence on tax aggressiveness. The result shows that capital intensity, inventory intensity, firm risk, audit committee, and independent commissioners have no influence on tax aggressiveness. The larger the size of the company, the more aggressive the company to the tax burden paid. Implications of this research for managerial, management can consider human resources where the larger the size of the company certainly has credible human resources to make good tax planning so tax expense can be small. This research adds the audit committee and independent commissioners variables.